Central and Obstructive Apneas in Heart Failure With Reduced, Mid-Range and Preserved Ejection Fraction - Borrelli, Chiara; Gentile, Francesco; Sciarrone, Paolo; Mirizzi, Gianluca; Vergaro, Giuseppe; Ghionzoli, Nicolò; Bramanti, Francesca; Iudice, Giovanni; Passino, Claudio; Emdin, Michele; Giannoni, Alberto (Frontiers in Cardiovascular Medicine, 2019)
Background Although central apneas (CA) and obstructive apneas (OA) are highly prevalent in heart failure (HF), a comparison of apnea prevalence, predictors and clinical correlates in the whole HF spectrum, including HF with reduced ejection fraction (HFrEF), mid-range EF (HFmrEF) and preserved EF (HFpEF) has never been carried out so far. Materials and methods 700 HF patients were prospectively enrolled and then divided according to left ventricular EF (408 HFrEF, 117 HFmrEF, 175 HFpEF). All patients underwent a thorough evaluation including: 2D echocardiography; 24-hours Holter-ECG monitoring; cardiopulmonary exercise testing; neuro-hormonal assessment and 24-hour cardiorespiratory monitoring. Results In the whole population, prevalence of normal breathing (NB), CA and OA at daytime was 40%, 51%, and 9%, respectively, while at nighttime 15%, 55%, and 30%, respectively. When stratified according to left ventricular EF, CA prevalence decreased (daytime: 57% vs. 43% vs. 42%, p=0.001; nighttime: 66% vs. 48% vs. 34%, p<0.0001) from HFrEF to HFmrEF and HFpEF, while OA prevalence increased (daytime: 5% vs. 8% vs. 18%, p<0.0001; nighttime 20% vs. 29% vs. 53%, p<0.0001). In HFrEF, male gender and body mass index (BMI) were independent predictors of both CA and OA at nighttime, while age, New York Heart Association functional class and diastolic dysfunction of daytime CA. In HFmrEF and HFpEF male gender and systolic pulmonary artery pressure were independent predictors of CA at daytime, while hypertension predicted nighttime OA in HFpEF patients; no predictor of nighttime CA was identified. When compared to patients with NB, those with CA had higher neuro-hormonal activation in all HF subgroups. Moreover, in the HFrEF subgroup, patients with CA were older, more comorbid and with greater hemodynamic impairment while, in the HFmrEF and HFpEF subgroups, they had higher left atrial volumes and more severe diastolic dysfunction, respectively. When compared to patients with NB, those with OA were older and more comorbid independently from background EF. Conclusions Across the whole spectrum of HF, CA prevalence increases and OA decreases as left ventricular systolic dysfunction progresses. Different predictors and specific clinical characteristics might help to identify patients at risk of developing CA or OA in different HF phenotypes.